Peningkatan Kosakata Bahasa Jerman Melalui Media Cerita Pendek - Kisa Ramayana; Misnawaty Usman; Syamsu Rijal (Academic : Journal of Social and Educational Studies, 2023)
Abstract. This study aims to determine the increase in German vocabulary of grade XII students of SMA Negeri 8 Bulukumba through of the short stories medium. This research is a class action reseach consist of two cycles with each cycle consist of planing, implementation, observation and reflection stages. This data consists of two types, namely qualitative data in the form of observation data during the learning process and quantitative data in the form of test result to increase student’s German vocabulary. The average score of vocabulary mastery of grade XII students in cycle I was 55,52 and in cycle II increased to 81,04. The results of this study show that the use of short story media can increase the German vocabulary of grade XII students of SMA Negeri 8 Bulukumba.Keywords: Vocabulary, Learning Media, Short Stories, German